Interactive media use and youth learning, knowledge exchange and behavior - Dunkels, Elza 1960-; Fr?anberg, Gun-Marie; Hallgren, Camilla 1973- (Gale virtual reference library., 2011)
Outlines interactive media as an emerging research area, growing around young people and contemporary digital arenas. The field is growing in size, shape and complexity and the need for study is urgent.